Case report: A case of esophageal small cell carcinoma misdiagnosed as leiomyoma - Yan, Junjun; Xiao, Xifeng (Frontiers in Medicine, 2024)
Primary esophageal small cell carcinoma (PESC) is a rare, extremely aggressive malignancy characterized by rapid growth, early metastasis, and poor prognosis. This study presents a case of earlystage PESC that was initially misdiagnosed as an esophageal leiomyoma, which was observed as a submucosal tumor during gastroscopy. The patient subsequently underwent endoscopic submucosal dissection (ESD), which successfully achieved complete tumor resection. Histopathological analysis later confirmed the diagnosis of small cell carcinoma. Subsequent treatments were recommended; however, the patient declined these options and developed systemic metastases 16 months later, indicating progression to advanced disease and a poor prognosis. This case underscores the imperative to consider PESC in the differential diagnosis of submucosal esophageal lesions, especially when clinical suspicion is elevated, despite its rarity. Additionally, it highlights the challenges associated with the diagnosis and management of submucosal PESC and emphasizes the crucial role of early diagnosis in enhancing patient prognosis and survival rates.